A regionalização da produção agropecuária da microrregião geográfica de Ituiutaba/MG: uma análise sobre sua reorganização espacial - Silveira, Eduardo Marques (2017)
The transformations in the Brazilian agrarian space are intrinsic to its spatial organization, and along its history were necessary forthright factors for its development. Among the invigorating elements is pinpointed the modernization of agriculture, which has intensified since the 1980s. This is also present in the Geographical Microregion of Ituiutaba (MRG 017), the focus of this research. The agrarian space of MRG in analysis was changing, with the passage of time, which directly influenced the productive environment of the territorial units that compose it. In this sense, the present study had as its main goal to analyze the transformations occurring in the rural environment of the Geographical Microregion of Ituiutaba/MG, in the time scale ranging from 1990 to 2014. Specifically, it was sought to: a) understand how agriculture contributes to the spatial reorganization of the Geographical Microregion of Ituiutaba; b) understand how the Programa de Desenvolvimento dos Cerrados (POLOCENTRO) influenced the local/regional dynamics of this spatial cutout, and c) develop cartograms aiming at spatializing the reorganization of MRG's agricultural space through the use of geotechnologies. The scientific method used was the dialectic, since it understands the space through its transformations and dynamics. The MRG in analysis is composed of six cities, being them: Ituiutaba, Capinópolis, Santa Vitória, Ipiaçu, Cachoeira Dourada and Gurinhatã. In this way, the agrarian space of the MRG of Ituiutaba, throughout the history, underwent many transformations, from the way of crop establishment until the cultivars produced. It is cited, as an example, the insertion of two cultivars in this agrarian space, in different periods. Rice was one of the first crops to be cultivated intensively, that is, the MRG under analysis, in the 1970s, was considered a major producer of this grain, but some factors culminated in the decrease of its production, that is not expressive currently. After this period, in 1990 soybean were introduced, which was inserted in the agrarian space through public and private policies, and the technical advances should be highlighted as one of the main factors. Considering the diversity of the MRG under analysis, we selected some crops that best represented their agricultural production: sugarcane, corn, and soybean. Regarding the livestock activity, the dairy and beef cattle were analyzed. Thus, it is understood that MRG of Ituiutaba has undergone several transformations and these transformations have contributed to its socioeconomic development and, through several factors, its agrarian space has reorganized, showing the productive diversity present in the territorial units that integrate the MRG of Ituiutaba.